Perancangan Proteksi Petir SUTET dengan Konsep Lightning Performance dan Kinerja Arrester - Tri Sakti Adiwibowo (Energi & Kelistrikan, 2019)
Lightning surges often occur on the 500 kV SUTET (Extra High Voltage Air Line) transmission line. Therefore a reliable protection system design is needed to minimize damage due to lightning surge disruption and to maintain continuity in power flow. The authors use the concept of lightning performance and arrester performance as parameters for its reliability design. In this research, the concepts of lightning performance and arrester performance are used as parameters for their reliability design. In this case, the high category IKL (Isokreaunic Level) is used, which is 91 strikes / km2 / year. In determining the design of substation equipment, the performance of arresters at SUTET 500 kV is also analyzed by using the margin protection formula. Based on the arrester performance analysis and calculation of the protection margin, the protection system in GITET (Extra High Voltage Main Station) is more appropriate to use MOV EXLIM 550 kV arresters, power transformers (BIL: 1425kV), CVT (BIL: 1550 kV), CT (BIL: 1550 kV), BSI (BIL: 1550 kV), and CB (BIL: 1550 kV) with a protection margin of more than 20%